The sustainable land management program in the Ethiopian highlands: An evaluation of its impact on crop production - Schmidt, Emily; Tadesse, Fanaye (International Food Policy Research Institute, 2017)
This Working paper has been published as a journal article, available at https://hdl.handle.net/10568/145927